In healthy normotensive subjects age and blood pressure better predict subclinical vascular and cardiac organ damage than atherosclerosis biomarkers. (3rd September 2018) - Maloberti, Alessandro; Farina, Francesca; Carbonaro, Marco; Piccinelli, Enrico; Bassi, Ilaria; Pansera, Francesco; Grassi, Guido; Mancia, Giuseppe; Palestini, Paola; Giannattasio, Cristina
Abstract: Purpose: Only few studies evaluated biomarkers useful for defining the cardiovascular risk of a subject in a pre-clinical condition (i.e. healthy subjects). In this context we sought to determine the relationships of Plasminogen activator inhibitor type 1 (PAI‐1), P-Selectin, Tissue Inhibitors Metalloproteinases type 1 (TIMP-1) and Cystatin-C with subclinical Target Organ Damage (TOD) in normotensive and normoglycemic subjects without known cardiovascular and kidney diseases. Materials and Methods: 480 blood donors participated at the present analysis. TOD was evaluated as Pulse Wave Velocity (PWV), Left Ventricular Hypertrophy (LVH) and Intima Media Thickness (IMT) and carotid plaque presence) grouped together under carotid TOD. Results: 3.1% of the subjects showed a PWV higher than 10 m/sec with those subjects exerting significantly lower values of P-Selectine (0.068 ± 0.015 vs 0.08 ± 0.036 mg/L, p  = .014). 8.8% of the subjects showed carotid TOD that was associated with higher Cystatin-C values (0.67 ± 0.17 vs 0.63 ± 0.14 mg/L, p  = .045). Finally 23.8% of the subjects showed LVH with no significant differences regarding biomarkers. Despite some significant correlations between biomarkers and TOD, at the multivariate analysis none came out to be as significant predictor of the assessed TOD. Conclusions: in normotensive and normoglycemic healthy subjects, the evaluated biomarkers of atherosclerotic process didn't show any significant association with cardiac, carotid and vascular TOD while age and BP are its principal predictors.